Non-violence: a history beyond the myth - Losurdo, Domenico (Lexington Books, 2015)
This book embraces two centuries of the history of non-violence, reconstructing the great historical crises that this movement has faced. In this book the historical reconstruction is intertwined with the philosophical and psychological analysis of the moral dilemmas that great historical crises inevitably imply.